Utilitarian or Hedonic? A Cross Cultural Study in Online Shopping - Ozen, Hilal; Kodaz, Nil (Organizations and Markets in Emerging Economies, 2018)
With the irreversible effect of globalization, a growing number of websites today sell their products to more than one country. The effects of cross cultural differences on buying behaviors are widely acknowledged. Therefore, a consideration about attracting and retaining online consumers from different countries and cultures is gaining importance. This paper examines the roles of hedonic and utilitarian values in online shopping by comparing cross culturally the Turkish and US consumers. A total of 264 students from Turkey and USA participated in the survey. The findings showed that the online shopping behaviors of Turkish and USA consumers differ according to their hedonic and utilitarian values. While Turkish consumers use online retailers to socialize with others, the USA people use online shopping for relaxation purposes.
Keywords: Online shopping; hedonic value; utilitarian value; Turkey; USA